Selective conversion of fructose to 5-hydroxymethylfurfural over WO3/SnO2 catalysts. (20th July 2017) - Raveendra, G.; Surendar, M.; Sai Prasad, P. S.
Abstract : The effective solid acid catalyst WO3 /SnO2 has been synthesized and applied to the dehydration of fructose to HMF. Abstract : Biomass derived 5-hydroxymethylfurfural (HMF) has emerged as an important platform chemical for the production of value added chemicals and liquid fuels that are currently obtained from petroleum. The effective solid acid catalyst WO3 /SnO2 has been synthesized and applied to the dehydration of fructose to HMF. The synthesized samples were well-characterized by Fourier transform-infrared spectroscopy, laser Raman spectroscopy, X-ray diffraction, Brunauer–Emmett–Teller (BET) surface area analysis, TEM, Barrett–Joyner–Halenda pore size distribution, temperature programmed desorption of NH3 and pyridine FT-IR spectroscopy. The effects of various factors, such as reaction time, catalyst weight and temperature, on the formation of HMF have been investigated. Among these, 20 wt% WO3 /SnO2 exhibited excellent catalytic activity at 120 °C for 2 h and an HMF yield of 93% was obtained. The acidity measurements revealed that the increased surface acidic site density and the accessibility of the active sites made the catalysts excellent for the targeted conversion. The catalyst could be reused and its activity remained unaffected over five cycles.